1995
DOI: 10.1136/bmj.310.6981.693
|View full text |Cite
|
Sign up to set email alerts
|

Cross sectional study of effects of drinking green tea on cardiovascular and liver diseases

Abstract: Objective-To investigate the association between consumption ofgreen tea and various serum markers in a Japanese population, with special reference to preventive effects of green tea against cardiovascular disease and disorders ofthe liver.Design-Cross sectional study. Setting-Yoshimi, Japan. Subjects-1371 men aged over 40 years resident in Yoshimi and surveyed on their living habits including daily consumption of green tea. Their peripheral blood samples were subjected to several biochemical assays.Results-In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
214
1
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(231 citation statements)
references
References 28 publications
12
214
1
3
Order By: Relevance
“…Several observational studies have investigated the association between tea consumption and HDL‐C concentrations 24, 25, 26, 27, 28. The findings have been mixed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several observational studies have investigated the association between tea consumption and HDL‐C concentrations 24, 25, 26, 27, 28. The findings have been mixed.…”
Section: Discussionmentioning
confidence: 99%
“…The findings have been mixed. Some studies have reported no association between green or black tea and HDL‐C concentrations,26, 27, 28 whereas others have reported a significant positive association between tea consumption and HDL‐C concentration 24, 25. Of note, those observational studies were cross‐sectional study design, making it impossible to infer the temporal association between tea consumption and lipid profiles.…”
Section: Discussionmentioning
confidence: 99%
“…As yet, it is unclear whether these secondary plant metabolites are important nutritional antioxidants as little is known about their bioavailability, mechanism of uptake and consequences of biotransformation by intestinal¯ora (Hollman et al, 1997). However, epidemiological studies have implied that intakes of some phenolics are inversely related to risk of coronary heart disease (Hertog et al, 1993;Imai & Nakachi, 1995;Knekt et al, 1996). In addition, consumption of phenolicrich beverages such as red wine and tea are reported to transiently increase the ability of plasma to resist oxidative loads (Whitehead et al, 1995;Sera®ni et al, 1996) suggesting that at least a proportion of the phenolics in these beverages could have a role as antioxidants in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…More important, these results with traditional herbal medicine could open the door to a new frontier in the search for preventive agents of cancer and other lifestyle-related diseases. 20) …”
Section: Inhibition Of Tumor Promotion By Geraniinmentioning
confidence: 99%